Bifunctional CaCO3/HY Catalyst in the Simultaneous Cracking-Deoxygenation of Palm Oil to Diesel-Range Hydrocarbons - Rosyad Adrian Febriansyar; Teguh Riyanto; I. Istadi; Didi D. Anggoro; Bunjerd Jongsomjit (Universitas Pendidikan Indonesia, 2023)
Palm oil is a promising raw material for biofuel production using the simultaneous catalytic mechanism of the bifunctional cracking-deoxygenation reactions. Through the cracking-deoxygenation process, the chains of palmitic acid and oleic acid in the palm oil were converted to diesel-range hydrocarbons. The combination effects of CaCO3 and HY zeolite enhanced the bifunctional catalytic cracking-deoxygenation of palm oil into biofuel, because of the increasing acid and basic sites in the catalysts due to the synergistic roles of CaCO3 and HY. The introduction of CaCO3 on HY zeolite generated both a strong acid and strong basic sites simultaneously on the designed catalyst, which supports the bifunctional mechanisms of hybrid cracking-deoxygenation, respectively. The CaCO3 impregnated on the HY catalyst has a synergistic and bifunctional effect on the catalyst supporting cracking-deoxygenation reaction mechanisms as mentioned previously. The deoxygenation reaction required the bifunctional strong acid and strong basic sites on the CaCO3/HY catalyst through decarboxylation, decarbonylation, and hydrodeoxygenation reaction mechanisms. Meanwhile, the cracking reaction pathway was supported by the strong acid sites generated on the CaCO3/HY catalyst. In other words, the high acidity strength promotes diesel selectivity, whereas the high strength of basicity leads to the deoxygenation reaction.